THE EFFECTIVENESS OF TASK-BASED LANGUAGE TEACHING - Oblaqulova Dinora Jamshid qizi (Scholars Digest Publishing, 2024)
This article deals with the significance of task-based language teaching in an English classroom for second language learners. In this article, the origin of this teaching method is outlined and a detailed definition for this approach is provided to explain its use. Also, this paper highlights the sequence of the tasks that could be employed in an English classroom and showcases its main benefits for improving language skills. To improve the reliability of this article, some experiment results are analyzed and practical examples are given.
Keywords: task-based language teaching, second language, English classroom, pre-task, task cycle, post-task, evaluation, feedback.